Non-cross Bridge Viscoelastic Elements Contribute to Muscle Force and Work During Stretch-Shortening Cycles: Evidence From Whole Muscles and Permeabilized Fibers - Hessel, Anthony L.; Monroy, Jenna A.; Nishikawa, Kiisa C. (Frontiers in Physiology, 2021)
The sliding filament–swinging cross bridge theory of skeletal muscle contraction provides a reasonable description of muscle properties during isometric contractions at or near maximum isometric force. However, it fails to predict muscle force during dynamic length changes, implying that the model is not complete. Mounting evidence suggests that, along with cross bridges, a Ca2+-sensitive viscoelastic element, likely the titin protein, contributes to muscle force and work. The purpose of this study was to develop a multi-level approach deploying stretch-shortening cycles (SSCs) to test the hypothesis that, along with cross bridges, Ca2+-sensitive viscoelastic elements in sarcomeres contribute to force and work. Using whole soleus muscles from wild type and mdm mice, which carry a small deletion in the N2A region of titin, we measured the activation- and phase-dependence of enhanced force and work during SSCs with and without doublet stimuli. In wild type muscles, a doublet stimulus led to an increase in peak force and work per cycle, with the largest effects occurring for stimulation during the lengthening phase of SSCs. In contrast, mdm muscles showed neither doublet potentiation features, nor phase-dependence of activation. To further distinguish the contributions of cross bridge and non-cross bridge elements, we performed SSCs on permeabilized psoas fiber bundles activated to different levels using either [Ca2+] or [Ca2+] plus the myosin inhibitor BDM. Across activation levels ranging from 15 -100% of maximum isometric force, peak force and work per cycle were enhanced for fibers in [Ca2+] plus BDM compared to [Ca2+] alone at a corresponding activation level, suggesting a contribution from Ca2+-sensitive, non-cross bridge, viscoelastic elements. Taken together, our results suggest that a tunable viscoelastic element such as titin contributes to: 1) persistence of force at low [Ca2+] in doublet potentiation; 2) phase- and length-dependence of doublet potentiation observed in wild type muscles and the absence of these effects in mdm muscles; and 3) increased peak force and work per cycle in SSCs. We conclude that non-cross bridge viscoelastic elements, likely titin, contribute substantially to muscle force and work, as well as the phase-dependence of these quantities, during dynamic length changes.